Dissolution kinetics of propranolol hydrochloride 40 mg tablets under biowaiver conditions - Lennin R. Rodriguez-Saavedra; Pedro M. Alva-Plasencia; Yuri F. Curo-Vallejos; Segundo F. Saavedra-Suárez; Luis A. Chávez-Abanto; Olga E. Caballero-Aquiño; Miriam E. Gutiérrez-Ramos; Junior F. Sánchez-Bautista (GarVal Editorial Ltda., 2024)
Context: Ensuring the quality of a generic drug is essential for its commercialization. Propranolol hydrochloride is a drug in great demand on the market as it is widely used as an antihypertensive, antianginal, antiarrhythmic, and for the treatment of migraine, requiring a complete evaluation to determine equivalence. Aims: To evaluate the dissolution biopharmaceutical characteristic in multisource products marketed in the Peruvian market, taking Inderal® as a reference product. Methods: In vitro conditions are simulated using the USP apparatus II at 50 rpm and 900 mL of the dissolution media pH 1.2, 4.5, and 6.8 at 37°C. The dependent mathematical models were characterized by the Akaike information criterion, and the similarity was evaluated using the independent parameters (MDT, DE, and the similarity factor f2). Results: The average dissolution percentages demonstrate a difference between the multisource and the innovator in the three-dissolution media. The model that best characterizes the dissolution kinetics in all products is that of Hixson-Crowell. A significant difference was obtained in the MDT and DE between the innovative and multisource products and in the three-dissolution media. The similarity factor was not within the acceptable range for multisource products in the three-dissolution media. Conclusions: The 40 mg propranolol hydrochloride tablets included in the study are not equivalent in vitro to the innovative product and, therefore, are not interchangeable.